The Effect of CSR Disclosure and Environmental Performance on Financial Performance with Foreign Ownership as a Moderator (E-Jurnal Akuntansi, 2026)
Financial performance is a benchmark that describes the financial condition and success achieved. The purpose of this study is to empirically examine the influence of CSR disclosure and environmental performance on financial performance moderated by foreign ownership. This research conducted on companies that are members of the SRI-KEHATI Index of the BEI in period 20172020. Samples are selected by nonprobability sampling method and purposive sampling technique, the samples were 12 companies with 48 observations. Data collected through non-participant observation method. The analysis techniques used are descriptive statistics, classical assumptions, and moderated regression analysis (MRA). The results showed that CSR disclosure has a positive effect on financial performance. Environmental performance has a positive effect on financial performance. Foreign ownership can moderate with strengthens the effect of CSR disclosure and environmental performance on financial performance.
Keywords: Financial performance; CSR Disclosure; Environmental Performance; Foreign ownership